Place-based Socioscientific Issues Approach to Enhance Prospective Natural Sciences Teachers’ Critical Reasoning - Yokhebed Yokhebed; Mas Akhbar Faturrahman; Eka Ariyati; Reni Marlina; Erwina Oktavianty (Universitas Negeri Semarang, 2026)
Critical reasoning plays a crucial role in analyzing and evaluating available information and in formulating appropriate solutions to issues arising in communities today. This role can be enhanced through a place-based socioscientific issues (SSI) approach. This study aims to enhance prospective natural sciences teachers’ critical reasoning through a place-based SSI approach in West Kalimantan in two contexts: the use of kratom (Mitragyna speciosa Korth.) and tuak (rice wine). This study employed a quasi-experimental, non-equivalent control group pretest–posttest design and involved 64 students at Universitas Tanjungpura. Data were collected using a test comprising critical reasoning dimensions: information evaluation, complexity identification, information sources credibility assessment, and multiperspective. The profile of prospective natural sciences teachers’ critical reasoning showed improvement across all dimensions. The effectiveness of the place-based SSI approach showed a statistically significant improvement (p-value < 0.05) on the dimensions of complexity identification (large effect size), information sources credibility assessment (medium effect size), and multiperspective (medium effect size). The information evaluation dimension was insignificantly different (p-value > 0.05), despite a medium effect size. The findings show that a place-based SSI approach is effective for enhancing prospective natural sciences teachers’ critical reasoning. This study strengthens the SSI-based learning literature, develops scientifically literate citizens, and increases the quality of teacher education programs. Furthermore, this study contributes to Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education), by increasing the number of individuals with the skills necessary to navigate the ever-changing times and by enhancing the quality of prospective natural sciences teachers in West Kalimantan.